New contributions to Paracloeodes Day, 1955 (Ephemeroptera: Baetidae): description of a new species and of the adult stage of Paracloeodes carolinae Cruz, Salles & Hamada, 2018 - Santos, I.mara P.; Amaral, Igor F.; Salles, Frederico F. (Zootaxa, 2026)
Paracloeodes Day, 1955 is a Panamerican genus of mayflies, currently comprising 23 described species, with the greatest diversity occurring in the Neotropics. Among them, nymph-adult associations have been established only for nine species. As part of an ongoing project investigating mayfly diversity in poorly sampled areas in Brazil, a new species of Paracloeodes was identified, and the adults of Paracloeodes carolinae Cruz, Salles & Hamada, 2018 were reared from nymphs. The new species can be differentiated from the remaining species of the genus based on the following combination of characteristics: labrum with a deeply emarginate distomedial margin; glossa subequal to paraglossa, both rounded at apex; maxillary palp long (1.7× the length of galea-lacinia); presence of stout setae on the anterior surface of the foretarsus; and paraproct with 24–28 marginal spines. The male imago of P. carolinae can be distinguished from other imagos of the genus by the following combination of characteristics: turbinate portion of the compound eye yellow; stigmatic area of forewing with four veins not reaching the subcostal vein; and subgenital plate with a concave posterior margin and a pointed median spine. This study contributes to the taxonomic refinement of Paracloeodes and provides key insights into the life stages and distribution patterns of Neotropical mayflies.